2002
DOI: 10.1053/jhep.2002.36370
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotype 3 is cytopathic to hepatocytes: Reversal of hepatic steatosis after sustained therapeutic response

Abstract: On the basis of cross-sectional studies, it has been proposed that hepatic steatosis is a cytopathic effect of hepatitis C virus (HCV) genotype 3 but not genotype 1 infections. We tested this hypothesis by examining whether antiviral treatment altered hepatic steatosis in chronic hepatitis C. In 28 patients with genotype 1 and 34 with genotype 3 HCV, we determined the severity of steatosis in pre-and posttreatment liver biopsies using computerassisted morphometric image analysis as well as conventional semiqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
265
1
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(304 citation statements)
references
References 24 publications
27
265
1
11
Order By: Relevance
“…In a series of patients with genotype 3 and steatosis, a sustained virological response led to regression of steatosis in 91% of the cases, a much higher index than the 19% observed for those who did not present sustained virological response [6], making the cytopathic effect a more consistent cause of steatosis. Other authors have reported similar results [22,36].…”
Section: Steatosissupporting
confidence: 69%
“…In a series of patients with genotype 3 and steatosis, a sustained virological response led to regression of steatosis in 91% of the cases, a much higher index than the 19% observed for those who did not present sustained virological response [6], making the cytopathic effect a more consistent cause of steatosis. Other authors have reported similar results [22,36].…”
Section: Steatosissupporting
confidence: 69%
“…8 The development of cirrhosis in patients with HCV may be associated with regression of steatosis, 21 as has previously been documented in non-alcoholic steatohepatitis (NASH). 22,23 The mechanisms leading to a reduction in steatosis in the liver with cirrhosis remain Mihm et al 99 Yes Ratziu et al 18 Yes Fartoux et al 19 Yes Czaja et al 9 Yes Yes Yes Hourigan et al 10,11 Yes Yes Yes Adinolfi et al 12 Yes Yes Yes Yes Westin et al 13 Yes Weak Yes Yes Castera et al 14 Yes Yes Monto et al 15 Yes Yes Yes Kumar et al 100 Yes Camps et al 101 Yes (BMI) Kaserer et al 102 Yes Bressler et al 60 Yes (BMI) Rubbia-Brandt et al 28 Yes Yes Poynard et al 16 Yes Yes Yes Yes Yes Patton et al 17 Yes Yes Yes Yes Yes Nair et al 70 No* Marrero et al 103 Yes Ohata et al 74 Yes *Steatosis was a risk for HCC in alcoholic and cryptogenic cirrhosis only. Abbreviation: BMI, body mass index.…”
Section: Steatosis Influences the Progression Of Fibrosis In Chronic Hcvmentioning
confidence: 99%
“…14 Moreover, resolution of HCV infection after antiviral therapy is associated with a decrease in hepatic steatosis, particularly in patients with genotype 3. 15 Although hepatic steatosis has been considered a benign finding, recent studies have suggested that both steatosis and the more severe lesion of non-alcoholic steatohepatitis may be associated with progression of fibrosis in patients with hepatitis C. [16][17][18] However, many of the studies were cross-sectional and involved selected populations with unknown duration of steatosis. Furthermore, progression of fibrosis was estimated based on a single liver biopsy together with the clinical history of exposure and assumed that progression of fibrosis was linear over time.…”
mentioning
confidence: 99%